Modal Ventura Berbasis Wakaf: Inovasi Kebijakan Pembiayaan untuk Ekosistem Kewirausahaan Pesantren - Anas Alhifni; Martin Roestamy; Warizal; Biyati Ahwarumi; Asep Thobibudin Qolyubi (JURNAL ILMIAH GEMA PERENCANA, 2025)
This study proposes an innovative financing model that integrates waqf (awqaf) instruments with venture capital principles in response to the funding gap within the pesantren entrepreneurial ecosystem. The background of the problem indicates that although pesantren have significant economic potential, access to capital that is both Shariah-compliant and growth-oriented remains limited. The methodology employed is a qualitative multi-method approach, which includes an analysis of contemporary Islamic finance literature, case studies of productive waqf models, and the development of a conceptual framework through systematic modeling. The results and discussion demonstrate that the proposed Awqaf-Driven Venture Capital (Awqaf-VC) model has the potential to overcome traditional financing limitations by combining the perpetual nature of waqf with the strategic approach of venture capital. This framework is supported by a juridical analysis of Law No. 41 of 2004 concerning Waqf and the Financial Services Authority Regulation (POJK) No. 25 of 2023 concerning the Operation of Venture Capital Companies and Sharia Venture Capital Companies, which legally facilitates such a structure. The conclusion of this study is that the Awqaf-VC model can serve as a sustainable financing alternative that not only enhances the economic scalability of pesantren but also strengthens Shariah compliance in the digital age. The policy recommendation put forward is the development of derivative regulations that specifically govern the mechanisms for governance, risk mitigation, and fiscal incentives for nazhirs and managers of waqf-based Sharia venture capital funds.